Preliminary studies on the haematological parameters of cockerels fed raw and processed guinea corn (Sorghum bicolor) (2013)
The effect of feeding raw and ground guinea com [Sorghum bicolor L. Moench) on the haematological parameters of chicken was investigated in this study. Ten (10) 6-week old cockerels were randomly divided into two groups, A and B, and were fed raw and processed (dried and ground) guinea corn, respectively, for two weeks. Packed cell volume (PCV), Haemoglobin (Hb), Red blood cell count (RBC), White blood cell, count (WBC), neutrophils, eosinophils, lymphocyte and monocyte counts were determined before and after the duration of feeding the cockerels with guinea corn. Although significant changes were not observed in most of the haematological parameters, birds fed with processed guinea corn however had a significantly higher red blood cell (RBC) count than birds fed with the raw guinea corn. These findings suggest that feeding of processed guinea corn to cockerels may be more advantageous than feeding of raw guinea corn.